The legacy and other stories ebook - Layton, Edith (Untreed Reads, 2020)
Previously published individually, these four great novellas are collected in one book for the first time!"The Legacy"—Valerian Blackwood is summoned to his aged uncle's country estate to help the old man settle a problem with his heir. What Valerian finds is a mystery—and the love of his life. He only has to decide which is more important to him: solving the mystery or winning his lady."Buried Treasure"—What is Hannah Jenkins to make of the wildly attractive silver-tongued man villagers bring to her family's house after he is found injured on the shore near her seacoast home? He says he was the victim of pirates. But who is the pirate, and who is the prey?"Something Blue"—June Heywood's coming wedding day is clouded by a vicious remark she overhears, causing her to wonder why the handsome and clever Lawrence, Lord Morrow, ever asked for her hand. Who should she believe? Gossip or her heart?"A Marriage of True Minds"—The bride's sister and the groom's brother, alike in temper, lock horns—all the while missing what their relatives can so plainly see.